HUBUNGAN KECANDUAN BERMAIN GAME ONLINE TERHADAP INTERAKSI SOSIAL PADA REMAJA - ANJASARI, EKA ARISTA; SRINADI, I GUSTI AYU MADE; NILAKUSMAWATI, DESAK PUTU EKA (E-Jurnal Matematika; Vol 9 No 3 (2020), 2020)
Social interaction in adolescents in the modern era is influenced by several factors in life, one of which is addiction to playing online games. This study aims to determine the relationship between factors addicted to playing online games on social interaction in teenagers. The data used in this study are primary data which are the results of questionnaires. The data processing technique used in this study is canonical correlation analysis. The sample in this study were adolescents aged 13 to 21 years and living in the city of Denpasar, with a total sample of 150 adolescents. The results showed that the addiction factor playing online games had a significant effect of 0.0000019 on social interaction in adolescents with a close relationship of 0.8058964.